2022
DOI: 10.1109/access.2020.3033997
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Analysis of Epidemic Situations Based on a Spatiotemporal Information Knowledge Graph of COVID-19

Abstract: In view of the lack of data association in spatiotemporal information analysis and the lack of spatiotemporal situation analysis in knowledge graphs, this paper combines the semantic web of the geographic knowledge graph with the visual analysis model of spatial information and puts forward the comprehensive utilization of the related technologies of the geographic knowledge graph and big data visual analysis. Then, it realizes the situational analysis of COVID-19 (Coronavirus Disease 2019) and the exploration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…This also directly defines the research basis for us. Jiang et al (2020) presented a knowledge graph system to interactively explore epidemic situations. Yang et al noticed that based on crowd movement and control measures may have an impact on the epidemic, so they proposed EpiMob (Yang et al 2022), a VA system which simulates the changes in human mobility and infection status.…”
Section: Visual Analytics Of Covid-19 Datamentioning
confidence: 99%
“…This also directly defines the research basis for us. Jiang et al (2020) presented a knowledge graph system to interactively explore epidemic situations. Yang et al noticed that based on crowd movement and control measures may have an impact on the epidemic, so they proposed EpiMob (Yang et al 2022), a VA system which simulates the changes in human mobility and infection status.…”
Section: Visual Analytics Of Covid-19 Datamentioning
confidence: 99%
“…KIM et al, 2021;SCARPONE et al, 2020;KWOK et al, 2021;BUJA et al, 2020;VAZ, 2021). Como exemplo, tem-se a pesquisa de Lenzen et al (2020) BHERWANI et al, 2021;ZHANG et al, 2020;SANGIORGIO;PARISI, 2020;GIANQUINTIERI et al, 2020;POURGHASEMI et al, 2020;SHAW et al, 2021;KARAIVANOV, 2020;PAPASTEFANOPOULOS;VICTOR OKHUESE, 2020;LINARDATOS;KOTSIANTIS, 2020;CHENG et al, 2020;CHINAZZI et al, 2020;KONICEK et al, 2020;JIANG et al, 2020;PANG et al, 2021;ZHOU et al, 2020).…”
Section: A Dimensão Socialunclassified
“…These data are used to understand issues surrounding COVID-19 and to guide related decision-making. In [34] an analysis of the COVID-19 patients’ situations and their relationships is designed. Combining the semantic web of the geographic knowledge graph and the visual analysis model of geographic information, this work is useful in community prediction, discovering patients’ relationships, the analysis of the spatiotemporal distribution of patients, and the prevention and control of high-risk groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study found out that despite the stay-at-home orders issued by the organizations, the role of friends and families should be emphasized to promote compliance to the protocols [45] . As such relationships are mainly realized in social media, systematic and structural analysis of its content is very important [34] .…”
Section: Summary and General Analysismentioning
confidence: 99%